Implementasi Metode 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) Pada Gudang Regu Pengendalian Kebakaran Hutan dan Lahan PT. Wirakarya Sakti Distrik II - Agus Topo Subekti (LPPM Politeknik Jambi, 2019)
Currently on the production floor of PT. WKS has equipment that is not used in the work area, the work area is not well organized, and discipline regarding hygiene is very lacking resulting in the work process running poorly. Based on these conditions, it can be assessed that awareness of maintaining a work area is very minimal. One of the activities that companies can do to make improvements in the work area is by applying the 5S method. The 5S method is a basic approach in regulating the work environment, which essentially tries to eliminate waste so that an effective work environment is created. Based on the results of the 5S method audit can be given an improvement proposal to create a safe and comfortable work area. Based on the results of research and discussion, the implementation of the 5S method in the PT Wirakarya Sakti District II Company in the warehouse section of the Fire Control Regu can be summarized as follows: Seiri (concise), the application at this stage has not been implemented properly, because there are still irregular classifications of goods and there are still items that are not in accordance with the place. Seiton (neat), the application at this stage has not been implemented properly, because the placement of goods that are still difficult and slow in taking and returning goods and at each item placement there is no line boundary. Seiso (resik), the application at this stage has not been implemented properly, because places that are rarely noticed by people are still dirty and the cleaning tools that are needed by PIC warehouses are incomplete. Seiketsu (care), the application at this stage has not been implemented properly, because there is no usage information on the items that if used requires expertise. Shitsuke (diligently), the application at this stage has not been implemented properly, because the PIC warehouse has not made 5S a habit and...